Sedation with “non-sedating” antihistamines: four prescription-event monitoring studies in general practice - Mann, Ronald D (BMJ Group, 2000)
OBJECTIVES: To investigate the frequency with which sedation was reported in post-marketing surveillance studies of four second generation antihistamines: loratadine, cetirizine, fexofenadine, and acrivastine. DESIGN: Prescription-event monitoring studies. SETTING: Prescriptions were obtained for each cohort in the immediate post-marketing period. SUBJECTS: Event data were obtained for a total of 43 363 patients. MAIN OUTCOME MEASURE: Reporting of sedation or drowsiness. RESULTS: The odds ratios (adjusted for age and sex) for the incidence of sedation were 0.63 (95% confidence interval 0.36 to 1.11; P=0.1) for fexofenadine; 2.79 (1.69 to 4.58; P<0.0001) for acrivastine, and 3.53 (2.07 to 5.42; P<0.0001) for cetirizine compared with loratadine. No increased risk of accident or injury was evident with any of the four drugs. CONCLUSIONS: Although the risk of sedation was low with all four drugs, fexofenadine and loratadine may be more appropriate for people working in safety critical jobs.